Manganese Superoxide Dismutase Acetylation and Regulation of Protein Structure in Breast Cancer Biology and Therapy - Meredith M. Ogle; Rolando Trevino; Joseph Schell; Mahboubeh Varmazyad; Nobuo Horikoshi; David Gius (MDPI AG, 2022)
The loss and/or dysregulation of several cellular and mitochondrial antioxidants' expression or enzymatic activity, which leads to the aberrant physiological function of these proteins, has been shown to result in oxidative damage to cellular macromolecules. In this regard, it has been surmised that the disruption of mitochondrial networks responsible for maintaining normal metabolism is an established hallmark of cancer and a novel mechanism of therapy resistance. This altered metabolism leads to aberrant accumulation of reactive oxygen species (ROS), which, under specific physiological conditions, leads to a potential tumor-permissive cellular environment. In this regard, it is becoming increasingly clear that the loss or disruption of mitochondrial oxidant scavenging enzymes may be, in specific tumors, either an early event in transformation or exhibit tumor-promoting properties. One example of such an antioxidant enzyme is manganese superoxide dismutase (MnSOD, also referred to as SOD2), which detoxifies superoxide, a ROS that has been shown, when its normal physiological levels are disrupted, to lead to oncogenicity and therapy resistance. Here, we will also discuss how the acetylation of MnSOD leads to a change in detoxification function that leads to a cellular environment permissive for the development of lineage plasticity-like properties that may be one mechanism leading to tumorigenic and therapy-resistant phenotypes.